Pengukuran Kinerja Keuangan: Return on Equity (ROE) Dengan Atribusi Ekuitas - Marhaendra Kusuma; Prihat Assih; Diana Zuhroh (JURNAL ILMIAH MANAJEMEN & BISNIS, 2021)
The format of the balance sheet and income statement since the Indonesian IFRS convergence has changed with the addition of attribution of equity and comprehensive income. This change became the idea to develop the Return On Equity (ROE) formula. The purpose of this study is to empirically prove whether additional attribution information adds relevance value or is surprising, through analysis of the effect of ROE modification based on attribution of stock returns as a proxy for relevance value, with data on 504 companies listed on the IDX in 2016 2020. The results show that attribution equity and comprehensive income have value relevance for users. The novelty of this research is the modification of ROE with attribution of equity and comprehensive income, and the use of modified ROE to measure the value of relevance.